Analysis Of Causality Exchange Rate and Export Value In Indonesia (Empirical Study in 1997-2020) - Laksono.T.Y., R. Roosaleh; Dewabrata, Ignatius Oki; Arnan, Sendi Gusnandar; Bayunitri, Bunga Indah; Prayitno, Yogo Heru; Gunanta, Remon (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2023)
This study aims to analyze the causal relationship between the exchange rate and export value in Indonesia using time series data from 1997 to 2020. The analytical method that will be used in this research is the Granger Causality Test approach. The instruments used are the data normality test, the stationary test, the optimal lag test, and the Granger causality test. Based on the results of the research that has been done, it shows that from the output of the cointegration test in table 4.3 above, the trace statistic is 9.016078, which is smaller than the critical value (5%), which is 15.49471, and Prob. 0.3639 is less than 5 percent, whereas for the output of the Granger causality test above, at lag 1, it is known that the probability value (Prob.) of the relationship between export value and exchange rate is 0.4953; this result is greater than the significance level of 5 percent, so that from the output of the From these results, it can be concluded that there is no causal relationship between export values and exchange rates. So it can be concluded that if the exchange rate depreciates against foreign currencies, the export value will increase because Indonesia's export commodities compete in international markets, but on the contrary, it will reduce. In addition, based on observations and causality analysis from the results of data processing, it shows that there has been a one-way relationship between the exchange rate and the export value, meaning that the exchange rate will affect the export value but will, on the contrary, affect the export value. According to the results of the Granger Causality Test, the export value has no effect on the exchange rate.